2010
DOI: 10.1016/j.devcel.2010.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian Doublesex Homolog DMRT1 Is a Transcriptional Gatekeeper that Controls the Mitosis versus Meiosis Decision in Male Germ Cells

Abstract: Summary The switch from mitosis to meiosis is a unique feature of germ cell development. In mammals, meiotic initiation requires retinoic acid (RA), which activates meiotic inducers including Stra8, but how the switch to meiosis is controlled in male germ cells (spermatogonia) remains poorly understood. Here we examine the role of the Doublesex-related transcription factor DMRT1 in adult spermatogenesis using conditional gene targeting in the mouse. Loss of Dmrt1 causes spermatogonia to precociously exit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
321
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(338 citation statements)
references
References 62 publications
17
321
0
Order By: Relevance
“…In animals, nutrient deprivation is not the signal for meiotic entry. Instead, nutrient deprivation can affect the rate of stem cell proliferation, at least in part through insulin signaling (Drummond-Barbosa and Spradling, 2001;Hsu et al, 2008;Michaelson et al, 2010), with meiotic entry controlled by developmental pathways (Crittenden et al, 2002;Hansen et al, 2004b;Matson et al, 2010). Nevertheless, in animals, control of the mitotic cell cycle and core cell cycle regulators is also likely to be important in the switch from proliferation to meiosis.…”
Section: Introductionmentioning
confidence: 99%
“…In animals, nutrient deprivation is not the signal for meiotic entry. Instead, nutrient deprivation can affect the rate of stem cell proliferation, at least in part through insulin signaling (Drummond-Barbosa and Spradling, 2001;Hsu et al, 2008;Michaelson et al, 2010), with meiotic entry controlled by developmental pathways (Crittenden et al, 2002;Hansen et al, 2004b;Matson et al, 2010). Nevertheless, in animals, control of the mitotic cell cycle and core cell cycle regulators is also likely to be important in the switch from proliferation to meiosis.…”
Section: Introductionmentioning
confidence: 99%
“…These results provided further evidence for the agonistic activities for steroid receptors of PCP. In fish, steroid synthesis is mainly controlled by hypothalamic GnRH via pituitary-derived gonadotropic hormones (GtHs) and in turn the CYP enzymes (Nagahama et al, 1994;Yaron et al, 2003). Although the in silico results indicated no affinity of PCP with CYPs, we observed significantly up-regulated cyp11a mRNA and downregulated cyp17a, cyp19a mRNA in the liver of male rare minnow.…”
Section: Discussionmentioning
confidence: 47%
“…Although VTG is considered primarily synthesized in the liver, studies have shown that vtg mRNA could also be detected in extrahepatic tissues, especially the gonad, and could be induced following exposure to estrogenic chemicals (Wang et al, 2005). Dmrt1 plays critical role in male gonadal differentiation and maintenance (Ohtani et al, 2003;Matson et al, 2010) and it appears to be down-regulated in response to estrogen (Marchand et al, 2000) and up-regulated in response to androgen (Shibata et al, 2002). In the present study, vtg mRNA levels in liver and gonad and dmrt1 mRNA levels in gonad were also up-regulated in male fish upon 14-d exposure to PCP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was indicated that DMRT1 in Sertoli cells was essential to maintain testis determination (Matson et al, 2011) and regulate tubule morphology, spermatogenesis, and sperm function in mammals (Agbor et al, 2013). Additionally, DMRT1 in spermatogonia was demonstrated to determine whether spermatogonia undergo mitosis and spermatogonial differentiation or meiosis (Matson et al, 2010). Therefore, the intensive expression in Sertoli cells and mild expression in spermatogenic cells of CagDMRT1 during spermatogenesis of gibel carp should be most similar to expression characterization of mammalian DMRT1, suggesting that the DMRT1 expression characterization should be related to testis differentiation, testis development and spermatogenesis in gibel carp.…”
Section: Discussionmentioning
confidence: 99%